Motivation, experience and repeat visits: the case of Alfeñique Fair in Toluca, Estado de Mexico - Nava Valtierra, Brenda Nicole; Delgado Cruz, Alejandro; Palmas Castrejón, Yanelli Daniela (Acta Universitaria, 2022)
Gastronomic festivals have become popular because they offer a cultural experience through food. The objective of this research is to analyze the influence of motivations on the experience and the influence of this on repeat visits to the Feria del Alfeñique, in the city of Toluca, Mexico. During October and November 2021, a survey was applied to 399 participants, women (60.70%) and men (39.30%) who were mostly young people aged 18 to 30 years (59.8%) and adults aged 31 to 50 years (26.5%). Partial least squares structural equation modeling was used for data processing. The results show that social motivations are related to personal and cultural motivations and that positive experiences can lead to a second visit to the fair. In conclusion, this work has practical implications for the strengthening of this event within the context of the Day of the Dead.